Total Quality Management Practices and Technology Transfer in Malaysian Public University - jusoh, Ahmad; Yusuff, Rushami Zein; Mohtar, Shahimi (SBM ITB, 2007)
It is widely accepted that the implementation of Total Quality Management (TQM) as a management philosophy has significantly contributed to good management practice in business organization particularly in the manufacturing and service sectors. The applications of that concepts, techniques and tools have been successfully tailored to non-profit service or government-based organization. In the context of higher education institution, it has been seriously debated by the TQM scholars and academicians on the issue of to what extent TQM can be applied and how relevant its practices are to higher education's core business i.e. teaching and research. Despite having sufficient knowledge and research on TQM implementation in the scope of manufacturing practices and administration-related services, it is hard to find a research on TQM, which focuses on the scope of R&D at a university. This gap has to be filled because the management of research is a critical topic for universities worldwide. For developing countries such as Malaysia the need to have good management practice in R&D is even greater. Without effective research management, the task of becoming significant players in the global knowledge market will become harder. Thus, the first part of this paper will discuss the applicability of TQM and propose a theoretical framework or model of TQM to suit the need of R&D context. The constructs for the TQM framework are based on previous empirical studies and the evaluation criteria of world standard criteria such as MBNQA, EFQM, and QMS ISO 9000. The TQM constructs that will be proposed are leadership, strategic planning, student/stakeholder & industry focus, data & information management, staff management, process & system approach, partnership & resource and continuous improvement. The second part of the paper will discuss the performance indicators of R&D activities particularly in the context of public university. The review of international literatures stressed that the performance of R&D activities have to be measured. The current issue related to research performance at university is the level the research output that can be transferred to the stakeholders. Therefore, this study will use technology transfer framework to measure research performance such as publication, patents, royalty and Spin-off Company. Finally, this paper will conceptually develop a model that would show the relationship between the TQM practices in the area of research and the level of technology transfer.Â Keywords:Â TQM, Technology Transfer, Commercialization, University, Research Management